Mapping the (Invisible) Salaried Woman Architect: the Australian Parlour Research Project - Karen Lisa Burns; Justine Clark; Jullie Willis (Footprint)
Since the 1970s, feminist historians and polemicists have struggled to uncover the ordinary lives of women. They believe that gender ideals and biases are a critical part of the weft and weave of daily life. But the quotidian has been a restricted field in our discipline, often used to define a particular building type rather than the lives of architects. For example, we know little about the workdays of professionals or their labour in the workplace. The architectural office - its daily transactions and everyday culture - remains obscure. Even when represented in histories of the profession, the architectural office is filtered through a top-down lens trained on practice directors. The labour and lives of architecture’s male and female employees is unexplored terrain, but we could begin with the demographics: up to three-quarters of Australian women in architecture are salaried workers, continuing a historical trend. In the past, women generally worked for others. The gendering of salaried architectural workers raises questions about the relationship between gender and office work. Feminist historians and theorists have suggested that the office plays a role in forming gender ideals and practices. This paper endeavours to critically describe the lives and labour of women architects at the office, using survey and interview data from a large-scale Australian research project, publicly known through its website Parlour. This research inquires into gender disadvantage and investigates how gender ideals and norms shape the culture of the architectural workplace. The project’s research questions, evidence and explanations form the basis of this essay. The Parlour project is an ongoing platform for sharing information and research, but it gives particular voice to women’s experience in architecture, an experience largely shaped by salaried employment, studentship and the ownership of small practices.